The Festschrift Darkhei Noam : the Jews of Arab lands - Schapkow, Carsten, 1970-; Shepkaru, Shmuel; Levenson, Alan T.; Stillman, Norman A., 1945-; Erder, Yoram (Brill's series in Jewish studies, 2015)
The Festschrift Darkhei Noam: The Jews of Arab Lands presented to Norman (Noam) Stillman offers a coherent and thought-provoking discussion by eminent scholars in the field of both the history and culture of the Jews in the Islamic World from pre-modern to modern times. Based on primary sources the book speaks to the resilience, flexibility, and creativity of Jewish culture in Arab lands. The volume clearly addresses the areas of research Norman Stillman himself has considerably contributed to. Research foci of the book are on the flexibility of Jewish law in real life, Jewish cultural life particularly on material and musical culture, the role of women in these different societies, antisemitism and Jewish responses to hatred against the Jews, and antisemitism from ancient martyrdom to modern political Zionism.